Role of Computed Tomography Scan in the Management of Pediatric Acute Bacterial Meningitis: An Experience from a Tertiary Care Hospital in Lahore - Saliha Sarfaraz, Sadia Shabir, Bushra Ahmad, Zaeem Sohail Jafar, Muhammad Ali, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Acute Bacterial Meningitis (ABM) is not an uncommon ailment seen both in developing and developed countries. For the patients presenting with fever and seizures, the trend of doing CT scan brain is on the rise, which may not be justifiable in all cases. Objective: To determine the frequency of radiological findings on computed tomography (CT) of the brain among children presenting with acute bacterial meningitis. Materials & Methods: This cross-sectional study was conducted in Department of Pediatrics KEMU/Mayo Hospital Lahore after IRB approval. Patients with CSF-proven ABM whose CT brains had been performed were enrolled retrospectively, and the presence of hydrocephalus, cerebral infarct, edema and abscess as per CT report were recorded. Data were stratified for age, gender and duration of symptoms. Chi-square test was applied to compare findings in stratified groups. Results: A total of 165 ABM patients with a mean age of 6.2 ±1.3 years; 68.5% (113) males and 31.5% (52) females were included. CT brain was normal in 92 (55.8%), while 29 (17.6%) had cerebral edema, 20 (12.1%), 11 (6.7%) and 13 (7.9%) had cerebral infarct, hydrocephalus and cerebral abscess respectively. Conclusion: Computed Tomography is a useful tool for detecting intracranial complications of ABM. But routine use of CT-brain in every patient without clear indications should be avoided to decrease the risk of radiation exposure as well as to save resources. Keywords: Acute bacterial meningitis, Children, Cerebrospinal fluid, Computed tomography, complications